Pelatihan Komunikasi Daring yang Efektif bagi Anggota Asosiasi Pengusaha Patin UKM Indonesia - Maulana Amalia; Irzal Effendi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Catfish is a reigning top commodity both in the Indonesian market and overseas. Large-scale catfish farming companies have managed to communicate their products well, as evidenced by their effective online communication. However, that is not the case with small and medium-sized catfish farmers. Only some members of Asosiasi Pengusaha Patin/Catfish Indonesia (APCI) have successfully established online communication methods through websites and social media campaigns. This necessitates the rest of the members to be assisted in holding themselves up against tight competition especially in the global market through online communication training. This training program aims to raise awareness, knowledge, and understanding of the importance of small and medium-sized enterprises (SMEs) dabbling in catfish farming and production to display their products online. The methods used in this activity involve formulating initial research, designing the training materials and consultations, preparing the training program, and evaluating the program. This training program is successful in raising the awareness and understanding of the members of APCI and will be useful in further stages of implementation.